CAGR Analysis of Micro and Small Industries in West Java - Fahreza, Mohammad; Azhar Solihin, Shofwan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study analyzes growth trends and projects the development of Micro and Small Industries (MIS) in West Java for the 2023–2027 period. Using historical data from 2017 to 2022, the study identifies the Compound Annual Growth Rate (CAGR) for the number of business units, employment figures, and production value. The results indicate stable growth in the Micro and Small Industry sector, with a CAGR of 2.0% for the number of business units, 2.3% for employment figures, and 3.3% for production value. Based on historical data and projected inflation rates, the findings show a consistent increase in nominal production value, rising from approximately 5,400 billion IDR in 2023 to over 6,200 billion IDR in 2027. However, after adjusting for inflation, the real production value exhibits a flat to slightly declining trend. This indicates that the increase in nominal value is insufficient to counteract the depreciation of monetary value due to inflation. The projection graph illustrates that inflation has a significant impact on real economic outcomes. While there is growth in nominal value, the purchasing power and real profits generated by Micro and Small Industries may not increase significantly. These findings emphasize the importance of considering inflation in economic planning and decision-making, as well as the need for effective policies to control inflation to support sustainable economic growth in the Micro and Small Industry sector.